Evaluation of 12 strategies for obtaining second opinions to improve interpretation of breast histopathology: simulation study. (22nd June 2016) - Elmore, Joann G; Tosteson, Anna NA; Pepe, Margaret S; Longton, Gary M; Nelson, Heidi D; Geller, Berta; Carney, Patricia A; Onega, Tracy; Allison, Kimberly H; Jackson, Sara L; Weaver, Donald L
Abstract : Objective To evaluate the potential effect of second opinions on improving the accuracy of diagnostic interpretation of breast histopathology. Design Simulation study. Setting 12 different strategies for acquiring independent second opinions. Participants Interpretations of 240 breast biopsy specimens by 115 pathologists, one slide for each case, compared with reference diagnoses derived by expert consensus. Main outcome measures Misclassification rates for individual pathologists and for 12 simulated strategies for second opinions. Simulations compared accuracy of diagnoses from single pathologists with that of diagnoses based on pairing interpretations from first and second independent pathologists, where resolution of disagreements was by an independent third pathologist. 12 strategies were evaluated in which acquisition of second opinions depended on initial diagnoses, assessment of case difficulty or borderline characteristics, pathologists' clinical volumes, or whether a second opinion was required by policy or desired by the pathologists. The 240 cases included benign without atypia (10% non-proliferative, 20% proliferative without atypia), atypia (30%), ductal carcinoma in situ (DCIS, 30%), and invasive cancer (10%). Overall misclassification rates and agreement statistics depended on the composition of the test set, which included a higher prevalence of difficult cases than in typical practice. Results Misclassification rates significantly decreased (P<0.001) with all second opinion strategies except for the strategy limiting second opinions only to cases of invasive cancer. The overall misclassification rate decreased from 24.7% to 18.1% when all cases received second opinions (P<0.001). Obtaining both first and second opinions from pathologists with a high volume (≥10 breast biopsy specimens weekly) resulted in the lowest misclassification rate in this test set (14.3%, 95% confidence interval 10.9% to 18.0%). Obtaining second opinions only for cases with initial interpretations of atypia, DCIS, or invasive cancer decreased the over-interpretation of benign cases without atypia from 12.9% to 6.0%. Atypia cases had the highest misclassification rate after single interpretation (52.2%), remaining at more than 34% in all second opinion scenarios. Conclusion Second opinions can statistically significantly improve diagnostic agreement for pathologists' interpretations of breast biopsy specimens; however, variability in diagnosis will not be completely eliminated, especially for breast specimens with atypia.